Unveiling the Power of Words: A critical Discourse Analysis of Benjamin Netanyahu’s Speech at the United Nations General Assembly on September 27, 2024 - AlAsttal, Tasnim (International Journal of Linguistics, Literature and Translation, 2024)
This research paper aims to examine an extensive field of rhetoric concerning one of the most longstanding issues throughout contemporary history: the Israeli-Palestinian conflict. This study analyses Benjamin Netanyahu's speech before the United Nations General Assembly on September 27, 2024, with the objective of determining the rhetorical strategies employed and their impact on spreading the speaker's viewpoints. The main aim of the study is to investigate the utilization of power in Netanyahu's speech through textual, discursive, and cultural lenses. Therefore, the study employs a method of qualitative research and critical discourse analysis (CDA) for its analytical approach in order to accomplish that objective. Critical discourse analysis is employed in this study is to delve into Netanyahu’s speech to uncover the most important themes hidden within the text. The study makes use of Fairclough’s research on language in context, elaborating on the Three-Dimensional Model of Critical Discourse Analysis to conduct a detailed examination of the text at both the micro and macro levels. The findings demonstrate the effectiveness of discourse in spreading different points of view, influencing ideologies, and distorting history for the purpose of shaping the receivers' minds. Furthermore, the results of this research are expected to provide new perspectives on the relationship between language and power, along with politics and conflict.